Meta Synthesis: Ethnomathematics-Based PISA Questions on Secondary School Students' Mathematical Literacy - Aida Istiqomah; Zaenuri Zaenuri; Scolastika Mariani; Isnaini Rosyida (Universitas Teknokrat Indonesia, 2026)
Mathematical literacy is one of the skills assessed in the PISA test. The results of the PISA international assessment show that Indonesian students' mathematical literacy skills are not yet optimal. An effort to evaluate suboptimal mathematical literacy is to use questions with an ethnomathematics-based PISA framework. This study aims to synthesize various studies discussing ethnomathematics-based PISA questions used to assess the mathematical literacy of secondary school students. The research method used is a Literature Review with meta-synthesis techniques, which analyzes five selected articles published in 2020–2025 from the Scopus, Google Scholar, and Semantic Scholar databases. The inclusion criteria focused on qualitative studies with junior high and high school students as subjects that discussed mathematical literacy skills through a cultural context. The results of the study show that local cultural elements such as traditional food, Sidoarjo batik, and Gambang musical instruments are effective contextual media in connecting mathematical concepts with students' real lives. The most frequently appearing indicators of mathematical literacy are communication and mathematizing, while the indicators of reasoning and argument remain a major challenge for students. PISA questions with an ethnomathematics nuance are able to strengthen students' understanding of mathematics and instill local cultural values, thereby improving mathematical literacy. Thus, the integration of local culture in mathematics learning is an effective strategy for strengthening mathematical literacy skills and instilling cultural awareness in students in accordance with the PISA framework.